Analysis of combined prevention measures on HIV/AIDS incidence in Brazil (1980-2020) - Amaral, Gabriela Morais Celestino; Silva, Lucas Emanuel de Oliveira; Lessa, Simone Schwartz (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: The Human Immunodeficiency Virus (HIV) attacks the immune system, with acquired immunodeficiency syndrome (AIDS) being the most advanced clinical manifestation. Prevention strategies have evolved over time in response to scientific advancements. From an institutional perspective, the Unified Health System (SUS) provides tools for Combined Prevention to the entire Brazilian population, universally and free of charge. However, despite therapeutic advances, HIV/AIDS remains a significant public health problem. Objective: To analyze the impact of Combined Prevention measures on the incidence of HIV/AIDS in Brazil from 1980 to 2020. Methods: Quantitative, observational, longitudinal, and retrospective study. Descriptive and multivariate analyses were conducted, specifically employing linear regression techniques. The variables of interest included case incidence and the distribution of: tests for sexually transmitted infections (STIs), condoms, post-exposure prophylaxis for HIV (PEP), and pre-exposure prophylaxis for HIV (PrEP). Publicly available data were sourced from governmental repositories. Results: The country has accumulated 1,037,878 infection cases, with an average of 25,947 new cases per year. Regarding prophylaxis inputs, five out of six variables demonstrated a negative correlation with the incidence rate, with only the distribution of male condoms showing a positive correlation. The analysis of the effect of PrEP was not statistically significant. Conclusion: Brazil has reduced the incidence of the disease as Combined Prevention measures have advanced. More time is needed to assess the impact of PrEP on the incidence of new cases.